2000
DOI: 10.1038/35036406
|View full text |Cite
|
Sign up to set email alerts
|

Threonine 68 is required for radiation-induced phosphorylation and activation of Cds1

Abstract: In response to DNA damage, eukaryotic cells use a system of checkpoint controls to delay cell-cycle progression. Checkpoint delays provide time for repair of damaged DNA before its replication in S phase and before segregation of chromatids in M phase. The Cds1 (Chk2) tumour-suppressor protein has been implicated in certain checkpoint responses in mammalian cells. It directly phosphorylates and inactivates the mitosis-inducing phosphatase Cdc25 in vitro and is required to maintain the G2 arrest that is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
260
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(273 citation statements)
references
References 23 publications
9
260
0
4
Order By: Relevance
“…38,39 It has also been reported that following DNA damage ATM phosphorylates Chk2 at Thr68, an event critical for the activation of Chk2. [9][10][11][12][13] Here we show that Wip1 dephosphorylates Thr68 in Chk2 both in vivo and in vitro (Figures 2 and 3), and may act as a negative regulator of Chk2 (Figures 4b and 5). It has been reported that Ptc2 and Ptc3, two members of the PP2C family, bind to Rad53 and inactivate Rad53-dependent pathways in S. cerevisiae.…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 95%
See 3 more Smart Citations
“…38,39 It has also been reported that following DNA damage ATM phosphorylates Chk2 at Thr68, an event critical for the activation of Chk2. [9][10][11][12][13] Here we show that Wip1 dephosphorylates Thr68 in Chk2 both in vivo and in vitro (Figures 2 and 3), and may act as a negative regulator of Chk2 (Figures 4b and 5). It has been reported that Ptc2 and Ptc3, two members of the PP2C family, bind to Rad53 and inactivate Rad53-dependent pathways in S. cerevisiae.…”
Section: Antagonistic Effect Of Wip1 On Chk2-dependent Apoptosismentioning
confidence: 95%
“…It had been shown previously that phosphorylation of Chk2 on Thr68 is required for full activation of Chk2 via auto-(trans-or cis)phosphorylation. [9][10][11][12][13][31][32][33][34] We therefore investigated the role of Thr68-phosphorylation in the electrophoretic mobility shift of Chk2. We found that a Chk2 mutant, the alanine68 mutant (HA-Chk2 (T68A)), did not undergo the mobility shift when overexpressed (data not shown), indicating that Thr68 is required.…”
Section: Effect Of Wip1 On Thr68 Phosphorylation Of Chk2 Induced By Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Chk2 activation requires its phosphorylation by ATM at Thr68 within an amino-terminal SQ/TQ cluster Melchionna et al, 2000). This ATM-dependent phosphorylation event might be facilitated by the Plk3-mediated phosphorylation of Chk2-Ser73 (Bahassi el et al, 2006).…”
Section: Introductionmentioning
confidence: 99%